2011
DOI: 10.1098/rsbl.2011.0837
|View full text |Cite
|
Sign up to set email alerts
|

Brain development and predation: plastic responses depend on evolutionary history

Abstract: Although the brain is known to be a very plastic organ, the effects of common ecological interactions like predation or competition on brain development have remained largely unexplored. We reared nine-spined sticklebacks (Pungitius pungitius) from two coastal marine (predation-adapted) and two isolated pond (competition-adapted) populations in a factorial experiment, manipulating perceived predatory risk and food supply to see (i) if the treatments affected brain development and (ii) if there was population d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 25 publications
4
87
0
3
Order By: Relevance
“…Although several studies have demonstrated that population variation in brain size is correlated with predation [38,39], ours is the first to document the relationship between predators and brain cell proliferation in free-living vertebrates. We found that variation in forebrain cell proliferation in B. occidentalis correlated closely with predation pressure when examined both across all streams and in comparisons within drainages.…”
Section: Discussion (A) Predation Pressure Correlates Negatively Withmentioning
confidence: 99%
“…Although several studies have demonstrated that population variation in brain size is correlated with predation [38,39], ours is the first to document the relationship between predators and brain cell proliferation in free-living vertebrates. We found that variation in forebrain cell proliferation in B. occidentalis correlated closely with predation pressure when examined both across all streams and in comparisons within drainages.…”
Section: Discussion (A) Predation Pressure Correlates Negatively Withmentioning
confidence: 99%
“…For instance, local adaptation for large hippocampus size in chickadees (Parus rufescens) is thought to be the basis for enhanced food caching (Croston et al 2015), while hippocampus size in London taxi drivers increases with job experience (Maguire et al 2006;Woollett and Maguire 2011). And nine-spine sticklebacks (Gasterosteus aculeatus) show plastic responses in brain region size in relation to perceived predation pressure (Gonda et al 2012). Although guppy brains show phenotypic plasticity (Burns et al 2009b;Kotrschal et al 2012a), Trinidadian guppies are a textbook example of local adaptations in multiple traits (Bassar et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, these changes did not persist beyond metamorphosis . Similarly, nine-spined stickleback, Pungitius pungitius, developed larger bulbus olfactorius (chemosensory centre) regions in the brain when exposed to the odours of predatory perch (Gonda et al, 2012). Unfortunately, neither study explored whether these changes directly modified cognition or behaviour.…”
Section: Neuroplasticity and Cognitionmentioning
confidence: 99%